Analisis Adversity Quotient Siswa SMP Pada Pembelajaran Matematika - Lestari, Widiarti Dwi Lestari; Hanifah, Hanifah (Program Studi Pendidikan Matematika, Universitas Majalengka, 2025)
This study aims to describe the results of the analysis of junior high school students' adversity quotient in mathematics learning. This study uses a qualitative method with a descriptive approach designed to describe students' adversity quotient based on four indicators: Control, Origin & Ownership, Reach, Endurance. The population of this study was conducted on grade VIII students in Karawang city with a sample of 29 students. With data collection techniques through student adversity quotient questionnaires consisting of 30 statements, as well as observation and interviews. then analyzed using the percentage of student answers and interpreted descriptively based on the Likert scale. The results of the study, obtained an overall average percentage of 73.69% meaning that most students have an adversity quotient. If the higher the adversity quotient a person has, the greater their ability to survive in facing challenges when learning mathematics..